2013
DOI: 10.1097/ta.0b013e3182ab065b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of injury alone is not justified as the sole indication for computed tomographic imaging in blunt pediatric trauma

Abstract: Care management study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…We have previously shown that mechanism in and of itself should not direct CT imaging in trauma. 7 We have also shown that an elevated shock index pediatric age adjusted on presentation to the emergency department can accurately identify severely injured children. 6 Our current results suggest that combining SIPA with mechanism of injury can be used to guide decision making in an effort to reduce unnecessary CT imaging of children.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously shown that mechanism in and of itself should not direct CT imaging in trauma. 7 We have also shown that an elevated shock index pediatric age adjusted on presentation to the emergency department can accurately identify severely injured children. 6 Our current results suggest that combining SIPA with mechanism of injury can be used to guide decision making in an effort to reduce unnecessary CT imaging of children.…”
Section: Discussionmentioning
confidence: 96%
“…Hemodynamically stable patients with an abnormal physical examination, patients with altered levels of consciousness and patients whose mechanism of injury suspicious for internal organ injury undergo further evaluation with CT [ 7 ]. However, in the pediatric population, recent studies have shown that using CT scan, based solely on the mechanism of injury, is not justified [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…While in the management of a stable adult patient with blunt abdominal trauma the indications for a CT scan are established [ 2 ], its use in the pediatric population is still a matter of debate. It has been shown that the mechanism of injury as a sole indication for obtaining a CT scan in pediatric trauma victims does not clearly predict significant findings affecting patient management [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moore et al found that in children, CT imaging only based on mechanism of injury did not detect any serious positive findings. Therefore, the use of CT imaging in injured children in the absence of a physiologic or anatomic abnormality does not seem to be justified [29]. Auner und Marzi recommend that in children who are alert and assessable without clinical abnormalities and normal sonographic and radiographic findings a CT imaging is not necessary [3].…”
Section: Diagnostic Value Of Computed Tomographymentioning
confidence: 99%